MAL OF PUBLIC SERVICES IN THE FRAMEWORK OF WHOLE OF GOVERNMENT (WoG) AND E-GOVERNMENT IMPLEMENTATION IN INDONESIA - Ohan Suryana (Jurnal Ilmiah Kajian Keimigrasian, 2018)
The objective of this research is to know the effectiveness of Public Service Mall development as the implementation of the Whole of Government (WoG) Practice and the application of e-government concept in Indonesia. This qualitative research is conducted by implementing literature study approach through which the researchers gathered various sources of information. In addition, researchers also used a textual approach to the implementation of the effectiveness of Public Service Mall, Whole of Government (WoG) Practice and e-Government Applications. The study begins with a history of WoG development, then a discussion of WoG transformation towards e-government implementation, followed with opportunities and challenges in implementing e-government to Public Service Mall as a manifestation of e-government implementation. The results show that the development of Public Service Mall as the implementation of WoG practices in line with the concept of e-government has been appropriate and supports the principle of excellent public services.